Концепція методу Кельвіна на основі механо-електричного перетворення - Zharkikh, Yu. S.; Lysochenko, S. V. (Publishing house "Academperiodika", 2018)
The Kelvin method was based on the concept of the dynamic capacitor recharging by a contact potential difference. The present paper draws attention to the fact that the contact potential difference is not the same physical agent as the electrical potential difference due to the electromotive force. It cannot act as an active electrical voltage and, accordingly, cause the flow of an electric recharging current. The real reason for the appearance of a measured signal is the transformation of the electrode movement mechanical energy into the electric current energy. The current is generated due to periodic changes in the screening conditions of electrostatic charges above the investigated surface. Investigations are made of the method sensitivity to the amount of charges on the sample surface. It is shown that the measurement results are interpreted without invoking the ideas of the work function. Therefore, the method can besuccessfully used in studies of organic and biological materials and electrolytes. The proposed mechanism is applicable in both the investigations of macroscopic distributions of the surfacecharge and the atomic scale in the Kelvin probe force microscopy.